Determinación de las características fisicoquímicas del suero obtenido de la fabricación de mantequilla de leche de vaca - Alayo Rojas, Alfonso (2017)
Buttermilk for many years was considered as a waste and a pollutant, however, this view has changed radically because this by-product is a rich source of fats, protein and each of its components can be used as an input to enrich the milk that will be used for the production of dairy products. The objective of this research work. was to characterize the whey obtained from the manufacture of butter from cow's milk in order that depending on the chemical components it presents give it an additional use in the food industry. For this, the butter was made from cow's milk and then the serum was collected from the first waste, once this was obtained a sampling of each of the repetitions, where the Pasting was determined for the analysis of viscosity, solids totals, pH, acidity, density, fats and proteins, following AOAC methods. The average results showed pH = 6.70, lactic acid 0.16%, fat 1.66%, proteins 2.9%, caseins 2.36%, density 1.029 g / ml, solid extract 9.43 and viscosity with a k of 137.25 Pa.sn.